2023
DOI: 10.3390/children10030527
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utility of Hemoglobin, HALP Score, FAR Ratio, and Coagulation Parameters as Predictors for Preterm Birth

Abstract: Premature birth is a worldwide health issue, posing a high mortality risk for newborns, as well as causing emotional and financial difficulties, and long-term health issues for patients. Identifying effective predictors for preterm birth is essential for prolonging gestation or improving obstetric care. As invasive methods are costly, risky, and not universally available, we aim to assess the predictive capacity of various serum parameters in pregnant women during the third trimester, as a non-invasive alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Another study conducted by Hrubaru et al. during the third trimester of pregnancy demonstrated that FAR is a crucial determinant of the risk of preterm labor [33]. In our present study, we did not observe a significant difference in FAR between pregnant women at risk of preterm labor who delivered within 72 h and those who did not.…”
Section: Discussioncontrasting
confidence: 62%
“…Another study conducted by Hrubaru et al. during the third trimester of pregnancy demonstrated that FAR is a crucial determinant of the risk of preterm labor [33]. In our present study, we did not observe a significant difference in FAR between pregnant women at risk of preterm labor who delivered within 72 h and those who did not.…”
Section: Discussioncontrasting
confidence: 62%
“…In pregnancy, APS is associated with an increased risk of adverse obstetric outcomes. The immunological responses and inflammatory state induced by aPL can interfere with placental function, leading to fetal growth restriction, stillbirth, preeclampsia, and preterm birth [ 10 , 11 ]. Despite advances in understanding the role of aPL in pregnancy complications, the mechanistic underpinnings connecting aPL-associated thrombophilia and preterm birth remain only partially understood [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%